A new ADAMTS13 missense mutation (D1362V) in thrombotic thrombocytopenic purpura diagnosed during pregnancy - Calderazzo, Julio César (2012)
Thrombotic thrombocytopenic purpura (TTP) is a disease characterized by microvascular thrombosis, often associated with deficiency of ADAMTS13 activity. Hereditary TTP has been linked to mutations in the ADAMTS13 gene whereas the inhibition of ADAMTS13 activity by autoimmune antibodies has been associated with acquired TTP. We report the case of a woman with deficiency of ADAMTS13 activity that had been asymptomatic until her first severe TTP episode during her first pregnancy. Genetic analysis revealed a non described missense mutation of ADAMTS13. This mutation resulted in an aspartic acid to valine substitution (D1362V). To verify the mechanism of ADAMTS13 deficiency in this patient, the wild type and the D1362V ADAMTS13 mutant construct was expressed in HEK 293 cells. The D1362V substitution led to a defect of secretion (ADAMTS13 antigen level=8±3%, ADAMTS13 activity=0% in culture media), causing intracellular accumulation of the protease (ADAMTS13 antigen level=133±5%, ADAMTS13 activity=129±13%) compared to wild-type (WT) ADAMTS13 (ADAMTS13 antigen and activity=100%). The results showed that D1362V mutation in the second CUB (CUB-2) domain, encoded by exon 29, induces an ADAMTS13 plasmatic deficiency due to reduced secretion of the protease into the circulation. Our data suggested that the CUB-2 domain encoded by exon 29 is particularly important for ADAMTS13 secretion. Apparently, this severe ADAMTS13 plasmatic deficiency did not manage to lead to clinical manifestations given that the TTP triggering event was related to her first pregnancy.